Diversity of leafhoppers (Hemiptera: Cicadellidae) in experimental rice lots and associated weeds in Buenos Aires province, Argentina - Paradell, Susana Liria (2014)
We identified the species of Cicadellidae associated with rice fields from an agricultural experimental station of La Plata city, Argentina, and explored the diversity pattern of the leafhopper assemblage. Insects were obtained from rice and surrounding weeds between 2006 and 2010. Syncharina argentina (Berg) and Agalliana ensigera Oman were the most abundant species in rice and weeds, respectively. Diversity (H′), heterogeneity (D) and evenness (J) indices were estimated. There was a significant effect of crop cycle (2006 to 2010) and host plant (rice and weeds) on H′ and D, with the interaction between them being not significant. Evenness was similar in rice lots and weeds, but differed between crop cycles. The pattern of abundance of species within rice lots and weeds followed the logarithmic model. Possible explanations for this pattern are discussed. The importance of the presence of some species as vectors of plant pathogens is highlighted.